THE ROLE OF EXCELLENT SERVICE FOR THE SUPPLY CHAIN MANAGEMENT SECTION TOWARDS THE PERFORMANCE OF PT ANGKUTAN SUNGAI DANAU PENYEBARANGAN (INDONESIAN FERRY) - Saptono Kusdanu Waskito; Muji Rahayu (Dinasti Publisher, 2022)
The research wants to prove the role of Excellent Service in the Supply Chain Management Section on the Performance of PT Angkutan Sungai Danau Peberangan (Indonesian Ferry). The total population is 145 new students in 2020-2021, the sample is determined using the Slovin formula with a total of 107 people. The results showed that all data were from the Service Excellence variable and the PT ASDP (Indonesian Ferry) Performance variable. Declared valid and reliable. Corrected item-total correlation data for Service Excellence variable data is between 0.322 -0.538 greater than 0.300. So it is declared valid. Corrected item-total correlation data for PT ASDP (Indonesian Ferry) Performance variable data is between 0.308 -0.738 smaller than 0.300. declared valid. Cronbach's Alpha values ??for the Service Excellence and PT ASDP (Indonesian Ferry) performance variables are 0.802 and 0.929, respectively, which are greater than 0.700, so they are declared reliable. This means that the questionnaire used to collect data is a quality questionnaire and meets the requirements to collect data. The data proved to be normally distributed with asymp.sig values ??of 0.098 and 0.112. The simple linear regression equation is Y = a + b X .Y = 7.145 + 1.115 X. The meaning of this simple linear regression equation is: If without Service Excellence, then the Performance of PT ASDP (Indonesian Ferry) has a value of 7.145, but if it is added Service Excellence , then the performance value of PT ASDP (Indonesian Ferry) from 7.145 will increase to 7,145 + 1,115 by 8,260. So to improve the Performance of PT ASDP (Indonesia Ferry) it is necessary to increase the Service Excellence of the Supply Chain Management Work Unit. The author has proven that Service Excellence affects the Performance of PT ASDP (Indonesian Ferry) positively and significantly the calculated t test value is 20.279 > the t table value for 107 respondents according to Junaidi (2020:8) is 0.676. The arithmetic significance value is 0.000 <0.05.